2005
DOI: 10.1007/s10295-005-0257-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of salt-tolerant glutaminase from Stenotrophomonas maltophilia NYW-81 and its application in Japanese soy sauce fermentation

Abstract: Glutaminase from Stenotrophomonas maltophilia NYW-81 was purified to homogeneity with a final specific activity of 325 U/mg. The molecular mass of the native enzyme was estimated to be 41 kDa by gel filtration. A subunit molecular mass of 36 kDa was measured with SDS-PAGE, thus indicating that the native enzyme is a monomer. The N-terminal amino acid sequence of the enzyme was determined to be KEAETQQKLANVVILATGGTIA. Besides L: -glutamine, which was hydrolyzed with the highest specific activity (100%), L: -asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 19 publications
1
46
0
Order By: Relevance
“…The molecular weight of the enzyme determined in the present study is in agreement with that of Wakayama et al (2005), who reported a 36 kDa glutaminase from Stenotrophomonas maltophilia. The purified Lglutaminase also exhibited salt tolerance up to a concentration of 16% (w/v) and had a residual activity of 93.04% after incubation for two hours at 40…”
Section: Discussionsupporting
confidence: 92%
“…The molecular weight of the enzyme determined in the present study is in agreement with that of Wakayama et al (2005), who reported a 36 kDa glutaminase from Stenotrophomonas maltophilia. The purified Lglutaminase also exhibited salt tolerance up to a concentration of 16% (w/v) and had a residual activity of 93.04% after incubation for two hours at 40…”
Section: Discussionsupporting
confidence: 92%
“…17 . Contradicting report on glucose -mediated suppression of the LGlutaminase production in Achromobacteraceae 43 , S. maltophilia NYW-81 45 was also reported. Sucrose (Z. rouxii) and sorbital (B. bassiana BTMF S10) also supported L-Glutaminase production in addition to glucose.…”
Section: Effect Of Additional Carbon and Nitrogen Sources On L-glutammentioning
confidence: 89%
“…It was noticed that addition of yeast extract enhanced the LGlutaminase secretion by C. nodaensis 38 , B. bassiana BTMF S10 36 and Z. rouxii 48,49 .While Siva kumar et al 45 observed that S. rimosus prefers the malt extract for higher L-Glutaminase production. Apart from complex nitrogen sources, inorganic nitrogen compounds such as ammonium sulphate and urea enhanced the enzyme production in Achromobacteraceae and Providencia sp.…”
Section: Effect Of Additional Carbon and Nitrogen Sources On L-glutammentioning
confidence: 99%
“…Treatment of raw products with asparaginase before thermal treatment resulted in a 96-99 % drop of acrylamide formation [71,72]. Therefore, it is not surprising that L-glutaminase is researched as a catalyst for the production of fermented condiments such as Japanese soy sauce [73].…”
Section: Fungal Amidasesmentioning
confidence: 99%